"2x^2\\dfrac{\\partial^2 z}{\\partial x^2}-5xy\\dfrac{\\partial^2 z}{\\partial x \\partial y} + 2 y^2\\dfrac{\\partial^2 z}{\\partial y^2} + 2[ x \\dfrac{\\partial z}{\\partial x}+y\\dfrac{\\partial z}{\\partial y}]=0\\\\"
Reduce the equation to the canonical form:
"A=2x^2\\\\\nB=-2.5xy\\\\\nC=2y^2\\\\\n\\Delta= B^2-AC=6.25x^2y^2-4x^2y^2=2.25 y^2"
So, we have hyperbolic type of equation.
Now let introduce a replacement.
"2x^2(dy)^2+5xy(dxdy)+2y^2(dx)^2=0|divide \\space by \\space (dx)^2\\\\\n2x^2(\\dfrac{dy}{dx})^2 + 5xy(\\dfrac{dy}{dx}) + 2y^2=0\\\\\ny'_1=\\dfrac{-5xy+\\sqrt{D}}{4x^2}=\\dfrac{-y}{2x}=> \\eta=2x+y\\\\\ny'_2=\\dfrac{-5xy-\\sqrt{D}}{4x^2}=\\dfrac{-2y}{x}=>\\psi=x+2y\\\\"
Now rewrite equation in new parameters:
"\\dfrac{\\partial z}{\\partial x}=2\\dfrac{\\partial z}{\\partial \\eta}+\\dfrac{\\partial z}{\\partial \\psi}\\\\\n\\dfrac{\\partial z}{\\partial y}=\\dfrac{\\partial z}{\\partial \\eta}+2\\dfrac{\\partial z}{\\partial \\psi}\\\\\n\\dfrac{\\partial^2 z}{\\partial x^2}=4\\dfrac{\\partial^2 z}{\\partial \\eta^2}+4\\dfrac{\\partial^2 z}{\\partial \\psi \n\\partial \\eta}+\\dfrac{\\partial^2 z}{\\partial \\psi^2}\\\\\n\\dfrac{\\partial^2 z}{\\partial y^2}=\\dfrac{\\partial^2 z}{\\partial \\eta^2}+4\\dfrac{\\partial^2 z}{\\partial \\psi \\partial \\eta}+4\\dfrac{\\partial^2 z}{\\partial \\psi^2}\\\\\n\\dfrac{\\partial^2 z}{\\partial x \\partial y}=2\\dfrac{\\partial^2 z}{\\partial \\eta^2}+4\\dfrac{\\partial^2 z}{\\partial \\psi \\partial \\eta}+2\\dfrac{\\partial^2 z}{\\partial \\psi^2}\\\\\n\nOur \\space equation:\\\\\n\\dfrac{8\\eta^2 -8\\eta\\psi +2\\psi^2}{9}(4z_{\\eta\\eta}+4z_{\\eta \\psi}+z_{\\psi \\psi})-5\\dfrac{5\\psi\\eta-2\\psi^2-2\\eta^2}{9}(2\\dfrac{\\partial^2 z}{\\partial \\eta^2}+4\\dfrac{\\partial^2 z}{\\partial \\psi \\partial \\eta}+2\\dfrac{\\partial^2 z}{\\partial \\psi^2})+\\dfrac{8\\psi^2 -8\\eta\\psi +2\\eta^2}{9}(\\dfrac{\\partial^2 z}{\\partial \\eta^2}+4\\dfrac{\\partial^2 z}{\\partial \\psi \\partial \\eta}+4\\dfrac{\\partial^2 z}{\\partial \\psi^2})+2[\\dfrac{2\\eta-\\psi}{3}(2\\dfrac{\\partial z}{\\partial \\eta}+\\dfrac{\\partial z}{\\partial \\psi})+\\dfrac{2\\psi-\\eta}{3}(\\dfrac{\\partial z}{\\partial \\eta}+2\\dfrac{\\partial z}{\\partial \\psi})=0"
Comments
Leave a comment